The Cheshire & Merseyside Collaborative trainee-led on-call service: a review of safety and efficiency. Issue 8 (August 2021) - McLeavy, C.M.; O'Mahony, E.; Wide, J.; Razzaq, F.; Rowlands, P.; Curtis, J.M.; Paton, D.; Chunara, M.H.; Porter, L.
Abstract : AIM: To assess safety and efficiency of the Cheshire & Merseyside Collaborative, the largest trainee led on-call service in the UK, based on discrepancy rates and time taken to issue reports. MATERIALS & METHODS: All studies reported by the collaborative in a 4-week period were evaluated for discrepancy and the time taken to issue a report. These figures were compared against the Royal College of Radiologists (RCR) guidelines and a recent national audit of discrepancy rates. The time taken to report was measured against the National Institute of Health and Clinical Excellence (NICE) and Trauma Audit Research Network (TARN) guidelines. RESULTS: The overall discrepancy rates for the collaborative were 2.5% for minor discrepancies and 2% for major discrepancies, which is within the RCR standard. The median time taken to issue a report was 30 min, which is within the NICE and TARN 1-h targets. CONCLUSIONS: The Cheshire & Merseyside Collaborative can be deemed a safe and efficient way of delivering an out-of-hours radiology service. Highlights: The Collaborative has lower discrepancy rates than the RCR standards. The Collaborative issues reports in an average of 30 minutes. The Collaborative is safe and efficient at delivering on-call radiology services.